(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, we discuss the existence and continuous dependence on initial data of solutions for non-local random impulsive neutral stochastic integrodifferential delayed equations. First, we prove the existence of mild solutions to the equations by using Krasnoselskii's-Schaefer type fixed point theorem. Next, we prove the continuous dependence on initial data results under the Lipschitz condition on a bounded and closed interval. Finally, we propose an example to validate the obtained results.